Impact of Examined Lymph Node Count on Precise Staging and Long-term Survival After Neoadjuvant Therapy for Carcinoma of the Esophagus: A SEER Database Analysis - Bao, Tao; Bao, Lei; Guo, Wei (Frontiers in Surgery, 2022)
Purpose: To identify the optimal number of lymph nodes dissected during esophagectomy following neoadjuvant therapy for carcinoma of the esophagus by using the Surveillance, Epidemiology and End Results Registry (SEER) database. Patients and Methods: Patients who underwent neoadjuvant therapy plus esophagectomy with EC from 2001-2016 were analyzed retrospectively in the SEER database. We analyzed the correlation between the lymphadenectomy count and nodal stage migration and overall survival (OS) by using a binary logistic regression model and Cox proportional hazards regression. The curves of the odds ratios (ORs) of nodal stage migration and hazard ratios (HRs) of OS were smoothed using the LOWESS technique, and the cutoff points were determined by the Chow test. The OS curves were calculated with the Kaplan–Meier method. Results: Among the 4,765 patients analyzed in the SEER database, a median of 14 lymph nodes (IQR, 7-19) were harvested. There was a significantly proportional increase in nodal stage migration (OR, 1.017; 95% CI, 1.011 to 1.023; P<0.001) and serial improvements in OS among node-negative patients (HR, 0.983; 95% CI, 0.977 to 0.988; P<0.001) with an increased ELN count after adjusting for the T stage. The corresponding cutoff point of the 16 ELNs was calculated for the OR of stage migration by the Chow test. For those with node-negative and node-positive diseases, no significant trend of survival benefit that favored a more extensive lymphadenectomy was demonstrated (HR, 1.001; 95% CI, 0.989 to 1.012; P = 0.906; and HR, 0.996; 95% CI, 0.985 to 1.006; P = 0.405, respectively). Conclusion: On the basis of these results, we recommend that at least 16 ELNs be removed for accurate nodal staging as well as for obtaining a therapeutic benefit after neoadjuvant therapy for EC. Furthermore, once precise nodal staging has been achieved, patient survival does not improve with additional ELN dissection after nCRT, regardless of pathological nodal staging (negative or positive).